A STUDY ON VISUAL CONTENT OF INFOGRAPHIC MEDIA HIERARCHY AS TEACHING MATERIAL ON BIOLOGY MATERIAL - Nuzul Syarbini; Elsi Susilawati; Nur Agilia Mardhatillah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
The development of technology makes learning media to be interestingly used and makes the material to be easy to understand. An interestingly learning media is infographic media. Infographic media become an effective teaching material in biology learning. Infographic media is closely related to the visual role of hierarchy. Visual hierarchy is one aspect that eases readers to understand information in a structured and systematic manner. The method used in the research is exploratory descriptive. The researcher collected general information related to teaching materials on biology materials and research studies from UIN Alauddin Makassar Biology Education students who used infographic media as teaching materials. Analysis of visual literacy used the theory of visual hierarchy. In terms of visual hierarchy, three teaching material media have been implemented to a good visual hierarchy. The content through a combination of colors, shapes or elements, a good layout, and the selection of created text models becomes contrast. It is because a good understanding of the visual hierarchy can create an infographic that is not only aesthetic but also comfortable for readers to read. Infographic media teaching materials used in viral materials, the phylum Echinodermata, and the digestive system have followed an appropriate visual hierarchy as teaching material media. Of the three infographic media as teaching materials above, of course, they have followed the visual hierarchy.